The Effect of Perceived Value on Culture-Based Tourism In Istano Basa Pagaruyung on Revisit Intention - Rozi, Fakhrul; Wulung, Shandra Rama Panji (Journal of Tourism Education, 2022)
As a culture-based tourism destination, Istano Basa Pagaruyung attempted to enhance the strategy of domestic tourists’ revisit intention. Therefore, this study aimed to obtain findings regarding the Perceived Value, Revisit Intention, and the influence of Perceived Value on culture-based tourism at Istano Basa Pagaruyung on revisit intention. This type of research was descriptive and verification with explanatory survey methods. The samples in this study were 110 domestic tourists, using the incidental sampling technique because the target population was those who had visited Istano Basa Pagaruyung. The data analysis technique used was multiple regression analysis. The relusts obtained indicate that the description of Perceived Value variable had a significant effect on the revisit intention variable, and partially it was found that there were 2 sub-variables, namely social value and epistemic value, which had a significant effect on Revisit Intention. However, the two other dimensions, emotional value and conditional value which did not have significant direct effect on revisit intention. Tourists could receive social quality and knowledge about a culture very well so that they could become motivation or intentions to visit againAs a culture-based tourism destination, Istano Basa Pagaruyung attempted to enhance the strategy of domestic tourists’ revisit intention. Therefore, this study aimed to obtain findings regarding the Perceived Value, Revisit Intention, and the influence of Perceived Value on culture-based tourism at Istano Basa Pagaruyung on revisit intention. This type of research was descriptive and verification with explanatory survey methods. The samples in this study were 110 domestic tourists, using the incidental sampling technique because the target population was those who had visited Istano Basa Pagaruyung. The data analysis technique used was multiple regression analysis. The relusts obtained indicate that the description of Perceived Value variable had a significant effect on the revisit intention variable, and partially it was found that there were 2 sub-variables, namely social value and epistemic value, which had a significant effect on Revisit Intention. However, the two other dimensions, emotional value and conditional value which did not have significant direct effect on revisit intention. Tourists could receive social quality and knowledge about a culture very well so that they could become motivation or intentions to visit again